SIMULATION OF ELECTRONIC AND MAGNETIC PROPERTIES OF LOW-DIMENSIONAL MATERIALS WITH USE OF FIRST PRINCIPLES METHODS - M. S. Zelenina; O. A. Kozlova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The result of electronic and magnetic properties investigation of ZnO granular films and quasi-two-dimensional structures of TiS2 and TiSe2 were presented. Quantum-mechanical approach in software package VASP was used during the calculation procedure, in particular the method of augmented plane wave (PAW-method). The values of the electronic states’ density of the compounds were presented, the distribution of the magnetic density of ZnO granular films were shown.